1999
DOI: 10.3310/hta3130
|View full text |Cite
|
Sign up to set email alerts
|

'Early warning systems' for identifying new healthcare technologies.

Abstract: Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA web site (see overleaf). NHS R&D HTA Programme T he overall aim of the NHS R&D Health Technology Assessment (HTA) programme is to ensure that high-quality research information on the costs, effectiveness and broader impact of health technologies is produced in the most efficient way for those who use, manage and work in the NHS. Research is undertaken in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(35 citation statements)
references
References 133 publications
(135 reference statements)
0
33
0
2
Order By: Relevance
“…For the medical specialties assessed, we have found that more than 90 percent of the technologies identified were first published in field specific medical journals different to those high impact journals selected for study purposes. Even though this finding is not completely new, because it has been previously acknowledged that early case series, case reports or uncontrolled trials that influence early adopters are frequently published in many different specialized medical journals (15), this is the first time that the search yield of key research medical journals for identification of new or emerging technologies is quantitatively assessed. The findings show that these sources are relatively inefficient for early identification of new or emerging technologies.…”
Section: Discussionmentioning
confidence: 99%
“…For the medical specialties assessed, we have found that more than 90 percent of the technologies identified were first published in field specific medical journals different to those high impact journals selected for study purposes. Even though this finding is not completely new, because it has been previously acknowledged that early case series, case reports or uncontrolled trials that influence early adopters are frequently published in many different specialized medical journals (15), this is the first time that the search yield of key research medical journals for identification of new or emerging technologies is quantitatively assessed. The findings show that these sources are relatively inefficient for early identification of new or emerging technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Because these new technologies may be used in common procedures, involve expensive equipment, and require time of highly specialized providers, they can have a dramatic impact on health services. 32 Technological innovation, however, does not necessarily translate into improved health care delivery or end results of treatment. For image-guided spinal surgery, the actual benefits to surgeons and patients remain to be defined clearly.…”
mentioning
confidence: 99%
“…Medical devices -the distinction between new and emerging here is less clear -will be prior to marketing or within 6 months of marketing or marketed but <10% diffused or localised to a few centres [13]. This comes down to a time horizon of 0-5 years before introduction [10,14].…”
Section: Horizon Scanning Programs and Their Scopementioning
confidence: 99%
“…There are also several attempts to classify the huge number of sources offering information on health technologies. The most common is the classification into primary, secondary and tertiary sources, determined according to the proximity to the origin of innovation [14].…”
Section: Identificationmentioning
confidence: 99%
See 1 more Smart Citation